Diagnosa Middle-Income Trap Indonesia melalui Pendekatan Teori Realitas Terintegrasi (IRT): Analisis Kualitatif Komparatif Indonesia–Vietnam - M Shoim; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the persistence of the middle-income trap in Indonesia through the perspective of Integrated Reality Theory (IRT). Unlike conventional growth approaches that emphasize capital accumulation, IRT integrates five fundamental variables Energy, Information, Entropy, Consciousness, and Evolution into a systemic analytical framework. This research employs a qualitative method with conceptual and comparative analysis approaches. The data used are derived from secondary sources, including the World Bank, Transparency International, and the Asian Productivity Organization. Quantitative data are utilized as empirical illustrations to support the analysis rather than as a basis for causal inference. Indonesia is compared with Vietnam as a country that has demonstrated accelerated productivity growth and more effective economic transformation. The findings indicate that the persistence of the middle-income trap in Indonesia is largely influenced by high systemic entropy, which results in large-scale energy leakage. This condition is further exacerbated by low institutional consciousness and the slow pace of adaptive capacity toward change. These findings imply the need for a shift in policy orientation, from mere economic expansion toward comprehensive structural cleansing and reform.